Early population dynamics in classical biological control: establishment of the exotic parasitoid Torymus sinensis and control of its target pest, the chestnut gall wasp Dryocosmus kuriphilus, in France. Issue 5 (25th March 2018) - Borowiec, Nicolas; Thaon, Marcel; Brancaccio, Lisa; Cailleret, Benoît; Ris, Nicolas; Vercken, Elodie
Abstract: In response to the introduction and spread of the chestnut gall wasp Dryocosmus kuriphilus Yasumatsu (Hymenoptera: Cynipidae) in metropolitan France, including Corsica, the exotic parasitoid Torymus sinensis Kamijo (Hymenoptera: Torymidae) was deliberately introduced in more than 50 locations covering most of the areas of chestnut production. To test the impact of propagule pressure (i.e., the number and size of introductions) on establishment success and post‐release dynamics, the introductions were done according to three experimental modalities: (1) a single introduction of 100 females, (2) two sequential introductions of 50 females, or (3) a single introduction of 1 000 females. Post‐release surveys demonstrated a very high local establishment of T. sinensis, regardless of the introduction modality. Post‐introduction dynamics were found to follow a two‐phase process. First, early dynamics were characterized by an exponential growth of T. sinensis populations without a significant decrease in D. kuriphilus populations. Later, middle‐term dynamics indicated a global decrease in both D. kuriphilus and T. sinensis populations. Quite surprisingly, propagule pressure had a limited effect on post‐introduction dynamics, with a lasting demographic advantage for the largest introductions, but no influence of the number of introductions. Finally, site connectivity had a positive effect on T. sinensis population size, suggesting successful colonization and establishment at a wide spatial scale beyond the introduction sites. In addition, we observed that some T. sinensis exhibited a very short developmental time compared to the majority of the emerged individuals, which may be interpreted as a diversified bet hedging strategy against environmental stochasticity. These findings confirm the strong potential of T. sinensis for successful establishment and sustainable control of the chestnut gall wasp in Europe. Abstract : Establishment of insect populations, in the frame of biological control programmes and invasion of exotic species, involves demographic processes that are difficult to demonstrate in real‐life ecosystems. In this study, we studied in the field the effect of various modalities of releases on the establishment of an exotic parasitoid introduced to control an invasive exotic pest. Our findings confirm the strong potential of this parasitoid to establish and durably control pest populations in Europe.